Cone beam computed tomography as a conclusive examination of bilateral coronoid process hyperplasia. Report of three cases - Valenzuela, Carlos (2021)
Mandibular  coronoid  process  hyperplasia  (MCPH)  is  an  excessive  mandibular  coronoid  process  (MCP) growing, is infrequent and produces an asymptomatic mouth opening limitation due to the impaction of the MCP in the posterior portion of the zygomatic bone. MCPH is a possible diagnosis in patients with both progressive mouth opening and protrusive movement limitations. In the present article, cases of three patients with mouth opening limitation are reported. In cone-beam computed tomography (CBCT) examination, a uniform growing of coronoid processes was observed, which confirmed the diagnosis of bilateral MCPH. CBCT with large field of view allowed the determination of the final diagnosis, because the impaction of the MCP in the posterior portion of the zygomatic bone during mouth opening could be observed. Furthermore, CBCT allowed to distinguish between MCPH and neoplasia of MCP and/or neighboring anatomical structures